Hydrazone-Containing Triblock Copolymeric Micelles for pH-Controlled Drug Delivery - Qi, Peilan; Wu, Xiaohe; Liu, Lei; Yu, Huimin; Song, Shiyong (Frontiers in Pharmacology, 2018)
In this study, the structure-activity relationship of amphiphilic block copolymer micelles as nanosized drug delivery system was revealed. Firstly, a biodegradable triblock polymers PEG-DiHyd-PLA containing hydrazone bond was synthesized through the ring-opening polymerization. In this method, PEG-DiHyd-Phenol was used as the initiator and L-lactide as the monomer. Then, the polymeric micelles were formed and used as nano-drug carriers with pH sensitive. The structure and composition of the polymer were characterized by infrared (IR), nuclear magnetic resonance (1H-NMR) and gel permeation chromatography (GPC), we characterized the self- assembling process of the triblock polymers and the pH sensitivity of the micelles by the means of transmission electron microscopy (TEM), dynamic light scattering method (DLS). Doxorubicin (DOX) acts as the model drug, and we researched the capacities of drug loading and release in vitro of the micelles. MTT experiments showed that the blank micelles of PEG-DiHyd-PLA were not cytotoxic to tumor cells(HepG-2, MCF-7) and normal cell(L-02 cells), but the doxorubicin loaded ones displayed more toxicity than the ones without hydrazone, which was consistent to the further confocal laser scanning microscopy and flow cytometry stuy.